Correlation between lead exposure and cognitive function in 12-year-old children: a systematic review and meta-analysis - Heidari, Serve; Mostafaei, Shayan; Razazian, Nazanin; Rajati, Mojgan; Saeedi, Anahita; Rajati, Fatemeh (Environmental science and pollution research international, 2021)
Lead exposure as a toxic material especially in children can be recognized as a harmful factor for cognitive function system. This meta-analysis was conducted to estimate the lead exposure effect on cognitive function among 6979 children less than 12 years. The 16 studies were divided into two clusters according to “duration of exposure” and “dose” using k-means partitioning clustering algorithm. Then, subgroup analysis has been performed based on the clustered studies. According to the results of the k-means clustering, dose and duration of exposure were significant factors between all considered variables. A stronger negative significant pooled correlation was observed in higher dose and duration cluster in comparison with another cluster including lower dose and duration ( r = − 0.29, P -value < 0.001 vs . r = − 0.08, P -value < 0.001). Overall, a negative significant correlation was observed between lead exposure and cognitive function test score ( r = − 0.22, P -value < 0.001). This study confirms the negative effect of lead on cognitive function in children, but needed further investigations to achieve the safe dose and duration of the lead exposure.